Association of Hyperthyroidism with Tobacco Smoking - A Case-Control Study - Zahra Abbas , Zahra Abbas; Abdullah Nasir, Abdullah Nasir; M Daniyal Munawar, M Daniyal Munawar (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: To determine the association of tobacco smoking (whether active or passive) with hyperthyroidism, in patients presenting to the three tertiary health care facilities of Rawalpindi. Methods: A case-control study was conducted from 1 st December 2014 to 1st December 2017 at three tertiary care hospitals of Rawalpindi. 810 individuals were included in the study. 648 were established cases of euthyroid status. The other 162 were selected on the basis of their presenting signs and symptoms, established diagnoses of hyperthyroidism and decreased levels of thyroid stimulating hormone (TSH). Visits were made to surgical and medical ward patients whose state of health placed them in inclusion criteria, and detailed history was recorded for each individual. History included detailed questioning about personal habits, smoking of tobacco (whether done actively or passively), chewing of tobacco and specific questions that focused on exclusion criteria. A person consuming 1 pack of cigarettes per day/directly or exposed to the smoke of equivalent amounts of tobacco was labelled as actively-exposed. Results: Among 162 cases, 58 (36.25%) individuals were either active or passive smokers prior to diagnosis of hyperthyroidism. In 648 euthyroid individuals, 97 (14.96%) were found to be active or passive smokers. OR = 3.17, 95% CI = 0.347 to 0.414, P-value = <0.0001. Tobacco smokers/chewers were 3.17 times more likely to develop hyperthyroidism than non-tobacco users. Conclusion: Tobacco smoking is positively associated with likelihood of occurrence of hyperthyroidism. Keywords: Hyperthyroidism, tobacco smoking